PRIMEIRO REGISTRO DE OCORRÊNCIA DE ODONTEUCOILA MISIONERA DIAZ, 1974 (HYMENOPTERA, FIGITIDAE) PARA O BRASIL - Selegatto, A.; Perioto, N. W.; Lara, R. I. R.; Martinelli, N. M. [UNESP] (Instituto Biológico, 2021)
This study reports the first record of the occurrence of Odonteucoila misionera in to Brazil.

Este estudo relata, pela primeira vez, a ocorrência do eucoilíneo Odonteucoila misionera para o Brasil.
FIRST RECORD OF THE OCCURRENCE OF ODONTEUCOILA MISIONERA DIAZ, 1974 (HYMENOPTERA, FIGITIDAE) IN TO BRAZIL.
Keywords: Atlantic Rain Forest; Brazil; Eucoilinae; parasitoid; Brasil; Eucoilinae; Mata Atlântica; parasitóide